KEGAGALAN MEDIASI PERKARA PERCERAIAN DI PENGADILAN NEGERI MEMPAWAH - NIM. A1011221008, PUTRI REGITA WIJAKSONO (Jurnal Fatwa Hukum, 2025)
Abstract This study aims to analyze the factors causing mediation failure in divorce cases at the Mempawah District Court. Normatively, Supreme Court Regulation (PERMA) Number 1 of 2016 requires all civil cases to undergo mediation prior to litigation; however, based on data from 2023–2024, none of the mediated divorce cases at the Mempawah District Court resulted in a settlement. This research employs an empirical juridical method with a descriptive approach, utilizing primary data obtained through interviews with mediator judges and questionnaires distributed to litigating parties, as well as secondary data collected through literature review. The findings indicate that mediation failure is primarily caused by the absence of one of the parties particularly the defendant limitations in mediators’ capacity to manage emotional dynamics between the parties, and the lack of good faith and willingness to reconcile. Although the mediation procedures have been conducted in accordance with PERMA Number 1 of 2016, their effectiveness remains suboptimal due to obstacles originating mainly from the disputing parties. Keywords: Failure, Mediation, Divorce, District Court Abstrak Penelitian ini bertujuan untuk menganalisis faktor-faktor penyebab kegagalan mediasi dalam perkara perceraian di Pengadilan Negeri Mempawah. Secara normatif, PERMA Nomor 1 Tahun 2016 mewajibkan setiap perkara perdata untuk terlebih dahulu menempuh mediasi, namun berdasarkan data tahun 2023–2024 seluruh perkara perceraian yang dimediasi di Pengadilan Negeri Mempawah tidak mencapai kesepakatan damai. Penelitian ini menggunakan metode yuridis empiris dengan sifat deskriptif, menggunakan data primer yang diperoleh melalui wawancara dengan hakim mediator dan penyebaran kuesioner kepada para pihak, serta data sekunder melalui studi kepustakaan. Hasil penelitian menunjukkan bahwa kegagalan mediasi disebabkan oleh ketidakhadiran salah satu pihak, khususnya tergugat, keterbatasan kemampuan mediator dalam mengelola dinamika emosional para pihak, serta rendahnya itikad baik dan kesadaran para pihak untuk berdamai. Meskipun prosedur mediasi telah dilaksanakan sesuai ketentuan PERMA Nomor 1 Tahun 2016, efektivitasnya belum optimal karena hambatan utama berasal dari para pihak yang berperkara. Kata Kunci: Kegagalan, Mediasi, Perceraian, Pengadilan Negeri.